2015
DOI: 10.1159/000368666
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Patterns of Perilymphatic Space Enhancement in the Rat Inner Ear after Intratympanic Injection of Two Different Types of Gadolinium: A 9.4-Tesla Magnetic Resonance Study

Abstract: Objective: To compare the quality of perilymphatic enhancement in the rat inner ear after intratympanic injection of two types of gadolinium with a 9.4-tesla micro-MRI. Materials and Methods: Gadolinium was injected into the middle ear in 6 Sprague-Dawley rats via the transtympanic route. The left ear was injected with Gd-DO3A-butrol first, and then the right ear was injected with Gd-DOTA. MR images of the inner ear were acquired 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, and 4 h after intratympanic (IT) injection using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Gd-DTPA was selected for the first study (short-term comparison between two HA vehicles) because it has been reported to be superior in enhancing the whole cochlea (from apex to base) in the short term ( 4 ). Gd-DO3A-butrol was selected for the second study (long-term comparison between HA and standard-of-care vehicle) because it was reported to exhibit the strongest enhancement (in the basal turn) over a longer duration ( 3 ). The Gd preparations were diluted to a final concentration of 0.5 mol/L in the first and second studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gd-DTPA was selected for the first study (short-term comparison between two HA vehicles) because it has been reported to be superior in enhancing the whole cochlea (from apex to base) in the short term ( 4 ). Gd-DO3A-butrol was selected for the second study (long-term comparison between HA and standard-of-care vehicle) because it was reported to exhibit the strongest enhancement (in the basal turn) over a longer duration ( 3 ). The Gd preparations were diluted to a final concentration of 0.5 mol/L in the first and second studies.…”
Section: Methodsmentioning
confidence: 99%
“…IT injection was performed as previously described ( 3 , 4 ). The animals were anesthetized with 33 mg/kg zoletil (Virbac, Westlake, TX, USA) and 8 mg/kg xylazine (Bayer AG, Leverkusen, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the steroid solution injected into the tympanic cavity could be discharged within tens of minutes through the auditory canal. As a consequence, the therapeutic effect of the steroid on the inner ear may not be sufficient [ 10 ]. To treat hearing loss, formulations that maintain a high steroid concentration in the tympanic cavity for a sufficient amount of time must be developed.…”
Section: Introductionmentioning
confidence: 99%